Six-axis Force–Torque Analysis of a Flexible-Tube Wrist for Misaligned Ports in Robotic EV Charging - Raihan Yusuf Rifansyah; Agus Heri Setya Budi; Hendri Maja Saputra (Faculty of Engineering and Informatics, Universitas Multimedia Nusantara, 2025)
This paper presents a systematic 6-axis force-torque characterization of a flexible-tube wrist for robotic electric vehicle (EV) charging under various angular misalignments. Robotic plug insertion often relies on simplified models that fail to capture the complex contact dynamics of compliant mechanisms, limiting system robustness. To address this, we developed an experimental platform based on a cartesian robot with a roll–pitch–yaw wrist to measure full force–torque profiles during quasi-static insertions with controlled misalignments ranging from −8° to +8° in pitch and yaw. The results reveal a highly non-linear and asymmetric response, quantitatively demonstrated by a contact onset that shifts from a maximum depth of 45.8 mm at 0° to as early as 31.8 mm at +8° yaw, and peak axial forces reaching -18 N in pitch and -24 N in yaw. This asymmetry has practical implication, where a -5-degree pitch resulted in insertion failure while an equivalent +5-degree was successful. From this dataset, unique and repeatable force signatures were identified for each condition, providing a foundational basis for hybrid control strategies with force sensing to handle the final delicate insertion